Estudio de factibilidad para la creación de un centro de acopio y enfriamiento de leche, producción y comercialización de quesos en beneficio de los pequeños productores de la parroquia Atahualpa cantón Quito - Hidalgo Castro, Edison Fabián (2014)
The present study tests the feasibility of creating a center for collection and cooling of milk, cheese production and marketing the benefit of small producers of milk, which was conducted field research in order to study the current situation of parish of Atahualpa , determining the economic, social and productive conditions . In the study , two surveys were conducted , the first to know what the producers are going to form the association, and the second is for the purpose of cheese market on the other hand an analysis was run to choose the Market Place , is well by its intense commercial activity cheeses are sold in Solanda neighborhoods in southern Quito .